SEROEPIDEMIOLOGY OF AVIAN INFLUNENZA H5N1 SUBTYPE IN BATS AS RESERVOIR THAT WILD LIVE IN LOMBOK ISLAND - Kholik; Lalu Faesal Fajri (JURNAL SANGKAREANG MATARAM, 2016)
Avian Influenza is a zoonotic disease. Bat had been reported as reservoir of Avian Influenza disease. The Purpose of this research is to explain about the Bats as reservoir of Avian Influenza H5N1 subtype Virus that wild live in Lombok Island. Descriptive Cross sectional Study with purposive sampling method was used in this research. The Population Targets in this research are the Four Bat Caves in Lombok (Tanjung Ringgit Bat Cave, Lembah Sempage Bat Cave, Pujut Bat Cave, and Ganggelang Bat Cave). The Bats was cuptured by net trap and sera was collected from Brachialis vein and than examination by Haemaglutination Inhibition Test (HI Test) to known Geometric Mean Titer (GMT) of Avian Influenza H5N1 subtype titer in RSHV Banyumulek. The Result showed 53 antibody positive against Avian Influenza H5N1 subtype Virus among 55 sera of bats was collected (96%) with GMT value is 23.68 - 29.32. This research describe that antibody of Avian Influenza H5N1 subtipe was detected in sera in the bats in Lombok Island with high titer. It is possible false positives when HI testing for their sialic acid residues on serum. serum treatment with Receptor Destroyer Enzyme (RDE) was needed for inactivation of non-specific inhibitors like Non-antibody molecules present in serum that are capable of binding to the influenzavirus HA.